The stages‐of‐change approach for prosocial behavior: Message tailoring to encourage blood donation - Hong, Ji Mi; Lee, Wei‐Na (Journal of applied social psychology, 2021)
This research applied the Trans‐Theoretical Model and the Construal Level Theory to framing messages for blood donation. People can be at different degrees of readiness for blood donation and are, therefore, dispersed into discrete stages of change. These stages of change correspond to varying psychological distances that define the extent to which a person's thinking on the suggested behavior is (high construal level) or concrete (low construal level). Differences in psychological distance thus affect whether individuals focus on how easy it is to donate blood (feasibility) or on why it is important to donate blood (desirability) in the ad message. This research conducted two studies using a 2 (types of message: feasibility vs. desirability—manipulated) × 3 (stages of change: pre‐contemplation vs. contemplation/preparation vs. action/maintenance—measured) between‐subject, randomly assigned factorial design experiment. The results of both studies showed that for individuals in the pre‐contemplation stage, desirability, rather than feasibility, messages were more likely to produce favorable attitudes toward the ad, its sponsoring organization, and blood donation behavior itself, whereas the opposite was true for those in the action/maintenance stage. Those differences were weakened or not observed for those in the contemplation/preparation stage. These patterns of interaction were not replicated for behavioral intention. Collectively, these findings suggest that tailoring a message according to the intended audience's stage of change should promote positive attitudes for blood donation. Meanwhile, future research is needed to bridge the attitude‐behavior gap when it comes to blood donation.